Impact of Innovation on Profitability and Firm Value in Manufacturing Companies of the Food and Beverage Subsector - Putri Delima Sari; Insyirah Putikadea (Publikasi Inspirasi Indonesia, 2025)
This study aims to analyze the effect of innovation on profitability and firm value. The independent variables include innovation, while the dependent variables are profitability and firm value. This study focuses on food and beverage companies listed on the Indonesia Stock Exchange (IDX) during the period 2020–2022. This type of research is quantitative research. The sampling technique uses the purposive sampling method so that 30 companies can be obtained which are then analyzed using SPSS 26. The results of the study indicate that innovation does not have a significant effect on profitability, and innovation does not affect firm value.